Briefwechsel, Band 2, Briefe 1693-1698 - Thomasius, Christian 1655-1728 (Briefwechsel, 2020)
The correspondence of Christian Thomasius is a hitherto unknown source of material for the scholarly culture of the late 17th and early 18th centuries. It provides insight into the communicational structures of the res publica litteraria of the early Enlightenment, and it allows readers to reconstruct the genesis of theoretical and practical problems, along with their resolutions, in the context of social and political change